Identification and validation of lead compounds against furin - HABIRAMI T.; RATHI SUGANYA P. (International Journal of Pharma and Bio Sciences, 2016)
Most of the proteins are synthesized as inactive proforms requires a proteolytic process to render them active. Proprotein convertases (PCs) are a family of serine proteases capable of activating substrates. Furin is a family of subtilisin-like proprotein convertases (PCs) which is calcium-dependent serine endoprotease. It is enriched in Golgi apparatus that cleaves protein to active or mature form. It is utilized by many numbers of pathogens (HIV, influenza, dengue fever, Ebola, Marburg virus) to become fully functional. Evolutionary studies of furin have been done to identify the non-conserved sequences across multiple species, which is used as an active site for docking studies. The known furin inhibitors are investigated with virtual screening and the compounds are screened based on QikProp and Lipinski’s Rule of 5. More than 19000 unique natural small molecules from ZINC database and marine compounds from SWMD were screened with two-point Pharmacophore, comprising one ring and one hydrogen donor. Binding modes of these molecules were investigated with a multistep molecular docking approach using Glide software. ZINC18087726, ZINC20390250, BS053, GA009 and BS051 may be potential inhibitors of furin. These Screened hits were further analyzed based on their docking score, protein-ligand interaction and validated by their ADME properties and prime/MMGBSA. And stability of ligand – protein complex is estimated using molecular dynamics.